The Significance of Socially Constructed Behaviors to Modern Identities on Em Beihold’s "City of Angels" - Pujimahanani, Cahyaningsih; Hasana, Firdausy Alya; Rafiuddin, Rizal; Pakerti, Brillyan Luhur; Pasopati, Rommel Utungga (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
This article examines perspectives of modern identities in matters of socially constructed behaviors in the song of Em Beihold entitled City of Angels. People recently are attempting to attain a similar level of status and recognition by imitating these figures in appearances, behaviors, and lifestyles. This idea is also reflected on City of Angels is a song by Em Beihold released in 2020 that tells many people faking themselves by trying to imitate other people’s attitude and behavior when she working in Los Angeles. Through qualitative method and explorative approach in cultural studies, this journal analyzes modern people shaping their identities by imitating other people’s lifestyle and behavior. It is since people are told to always follow the trends to be more modern. In conclusion, in today’s world there is no more original identity, but constructed by imitating any preferred figure or condition with a certain attitude. Modern identities never stand alone, but are supported by socially constructed behaviors.